Luminescent substances from ancient history up to the end of the Mamlūk Era (1517 AD): A historical cultural study - Aljedani, Salih Maddah; Aloumi, Layla Sulaiman; Alqarni, Saad Saeed (International Journal of Innovative Research and Scientific Studies, 2026)
This study investigates the history of the discovery of luminescent substances in all their forms Ancient History up to the end of the Mamlūk era (1517 AD). The study then surveys observations from ancient civilizations including the earliest written references to fireflies and myths of luminous gemstones, such as the Buddhist night-shining jewel, Chinese magic painting, and Indian Vedic texts including the Mahabharata, and the Dhammapada that liken the firefly to transience. In Greece, Aristotle provided the first precise description of cold light from dead fish, fungi, and squid, differentiating it from incandescence, while the Roman Pliny the Elder extensively documented luminous mollusks, jellyfish, and gleaming gemstones based on direct observation and collected accounts. The study then shifts to the contributions of Arab and Muslim scholars. It begins with their documentation of the firefly, which they termed al-ḥubāḥib, recording linguistic and poetic descriptions by al-Jāḥiz, Ibn al-Baitār, and al-Damīrī, along with medicinal uses such as drying ear pus. Regarding marine luminescence, Ibn Battūta recorded the milky sea phenomenon in the Maldives, which locals associated with jinn, while Ibn Mājid, in his nautical poem, warned that glowing water hinders stellar altitude measurements. Ibn Wahshiyya and al-Ishbīli also noted trees that emit light at night, attributed to fungi, a phenomenon only recently recreated through genetic modification. In the domain of solid-state luminescence, the study uniquely highlights evidence from Arab heritage demonstrating knowledge of phosphorescence centuries before Brand. Al-Masʿūdi reported that ancient Egyptians coated copper spheres with chemical preparations to illuminate a tomb perpetually and described a ruby-like gemstone shining like a lamp. Al-Birūni, al-Qazwīnī, and al-Bākuwī confirmed the existence of stones that glow in the dark.